Computational fluid dynamics of impinging microjet for a needle-free skin scar treatment system. (1st October 2018) - Mohizin, Abdul; Roy, K.E.Reby; Lee, Donghee; Lee, Seung Ku; Kim, Jung Kyung
Abstract: A needle-free injection system is a non-invasive drug delivery system, and its applications are currently being extended from the delivery of vaccines and insulin. At present, they are gaining considerable popularity in skin remodeling treatment techniques, particularly in skin rejuvenation procedures involving the injection of aesthetic materials. Although some clinical studies have been conducted to understand the mechanisms involved in these practices, an extensive study from an engineering point of view has not yet been conducted. Herein, we aim to identify the key parameters in the needle-free injection process and study their effects on microjet characteristics. The total stagnation pressure of an impinging microjet determines the penetration capabilities of the injection and is monitored with the aid of both experimental and computational tools employed on a typical commercial injector. Our findings indicated that the filling ratio and driving pressure had significant impacts on the peak and average stagnation pressures of the impinging microjet. Furthermore, the penetration characteristics of a standard nozzle and injection fluid could be controlled by an effective combination of the filling level and driving pressure, and thus, they can be considered as vital parameters when performing skin remodeling procedures. Graphical abstract: